The use of digital dental calculator apps as an OHI-S calculation tool: a quasi-experimental - Moryka, Atthahira Nabila; Ningrum, Valendriyani; Lestari, Citra; Batsukh, Nomundari (Universitas Padjadjaran, 2024)
ABSTRACT Introduction: The utilization of applications as a tool for the calculation of dental and oral health indices has not yet been extensively explored. Consequently, researchers have proposed the development of the digital dental calculator application as a rapid and precise medium for the administration of oral health index surveys. Aim of this research is to analyze the use of digital dental calculator apps as an OHI-S calculation tool. Methods: The study design is quasi-experimental with a posttest-only group design. Convenient sampling was employed as the sampling technique, and the selected samples fulfilled the inclusion and exclusion criteria. The inclusion criteria were students of the dental profession at Baiturrahmah University, Indonesia, who were still enrolled in or had passed the periodontics module, while the exclusion criteria were students who did not participate in the full study (manual and digital). Results: The mean time taken to calculate OHI-S calculation results manually was 207.63 seconds, while the mean time taken to calculate the same results using the digital dental calculator application was 67.97 seconds. The results of the Mann-Whitney test indicate that there is a highly statistically significant difference between manual and digital calculations using the application, with a p-value of 0.000 (<0.05). Conclusion: There is a time difference between the use of digital and manual calculations for OHI-S calculations. The findings of this study indicated that the time required to perform OHI-S calculations using digital dental calculator applications was significantly shorter than that required for manual calculations.KEYWORDSoral hygiene index simplified (OHI-S), time duration, digital dental calculator